Unpacking the Impacts of a Universal Parenting Program on Child Behavior. Issue 2 (8th January 2021) - Altafim, Elisa Rachel P.; McCoy, Dana C.; Linhares, Maria Beatriz M.
Abstract : This study examined the theory of change of the ACT Raising Safe Kids parenting program, including whether intervention effects on children's behavior problems were explained by improvements in mothers' reported parenting practices, as well as whether baseline child behavior problems moderated these relations. Adult mothers of 3‐to 8‐year‐old Brazilian children were assigned to the intervention ( n = 97) or control ( n = 46) groups. Results showed that the intervention improved mothers' perceptions of their parenting practices (positive discipline, emotional and behavioral regulation, and communication). Intervention‐induced reductions in children's internalizing and externalizing behavior problems were mediated by improvements in mothers' emotional and behavioral regulation. Program effects were strongest for children with high levels of baseline behavior problems.